Laser-Stimulated Fluorescence in Paleontology - Kaye, Thomas G.; Falk, Amanda R.; Pittman, Michael; Sereno, Paul C.; Martin, Larry D.; Burnham, David A.; Gong, Enpu; Xu, Xing; Wang, Yinan (PLOS ONE, 2015)
Fluorescence using ultraviolet (UV) light has seen increased use as a tool in paleontology over the last decade. Laser-stimulated fluorescence (LSF) is a next generation technique that is emerging as a way to fluoresce paleontological specimens that remain dark under typical UV. A laser’s ability to concentrate very high flux rates both at the macroscopic and microscopic levels results in specimens fluorescing in ways a standard UV bulb cannot induce. Presented here are five paleontological case histories that illustrate the technique across a broad range of specimens and scales. Novel uses such as back-lighting opaque specimens to reveal detail and detection of specimens completely obscured by matrix are highlighted in these examples. The recent cost reductions in medium-power short wavelength lasers and use of standard photographic filters has now made this technique widely accessible to researchers. This technology has the potential to automate multiple aspects of paleontology, including preparation and sorting of microfossils. This represents a highly cost-effective way to address paleontology's preparatory bottleneck.